Preparation And Evaluation Of Copper Gambir Complexes As Antifouling Agent - Hamdan, Hairul Safley (2014)
Uncaria gambir plant has been studied and characterized as antifoulant agent in antifouling paint. Four different solvents namely ethyl acetate, ethyl acetate: ethanol (1:1), 50 % ethanol and water were used to extract Uncaria gambir in order to find out the total phenolic content (TPC), total flavonoid content (TFC) and condensed tannin content of the gambir extract. Extraction of gambir by ethyl acetate: ethanol (1:1) ( v/v) solvent produced 32.3 % yield and the highest TPC, TFC and condensed tannin content. Gambir extracts were reacted with copper(II) sulphate pentahydrate to produce copper gambir (CuG) complex and were evaluated as antifoulant pigment. The effect of copper dosage, pH solution, reaction temperature and reaction time in optimization of synthesis condition for copper gambir (CuG) complex were studied. The FTIR spectra and AAS analysis showed that CuG complex produced at pH 5.0 had shown the lowest copper content and low presence of copper(II) hydroxide. Synthesized CuG complexes at 60 °C and 30 min reaction time revealed that copper content in CuG complex increased as the pH solution of CuG increased. CuG complexes at pH 5.0 and pH 6.0 were chosen for comparison. Surface analysis through SEM portrayed significant changes in the morphology of gambir extract after reacted to produce CuG.